Family Tourism and its Role in Improving Uzbekistan's International Image (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes family tourism, its role and importance in the development of national tourism in Uzbekistan, and issues of organizing domestic and international tourism. The issue of the role of family tourism in enhancing the international image of Uzbekistan, in the physical and spiritual development of a person is considered.